Examination of the Pandemic Awareness Level and Approach to the Pandemic in Wrestlers - Sema Can; Erkan Demirkan; Mehmet İsmail Tosun; Mustafa Arıcı (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2024)
Study aim: Wrestling involves a high risk of transmission in terms of Covid-19 as it is performed using close one-to-one physical contact. This field research study examined wrestlers' approach to and awareness levels of the pandemic. Method: The study sample consists of 214 male wrestlers aged 19.15 ± 1.78 years who participated in the U-23 Turkish National Freestyle Wrestling Championship. The data was collected using a personal information form and the Pandemic Awareness Scale. The statistical analysis consisted of an independent sample t-test, descriptive statistics, and a One-Way ANOVA test for multi-group comparison. Results: Non-smokers and the wrestlers who complied with the precautions had statistically higher awareness score averages (p < 0.05). A statistically significant relationship between awareness scores and variables, including education level, being a national athlete, being diagnosed with Covid-19, losing a first-degree relative to Covid-19, having been vaccinated, and the number of vaccine doses (p > 0.05) was not found. Conclusion: The study findings indicate that the level of awareness of the pandemic is high among non-smokers and wrestlers who complied with the necessary precautions.